Prevention of postoperative pulmonary complications through intensive preoperative respiratory rehabilitation in patients with esophageal cancer. Issue 1 (12th March 2012) - Inoue, J.; Ono, R.; Makiura, D.; Kashiwa‐Motoyama, M.; Miura, Y.; Usami, M.; Nakamura, T.; Imanishi, T.; Kuroda, D.
Summary Postoperative pulmonary complications (PPCs) after esophagectomy have been reported to occur in 15.9–30% of patients and lead to increased postoperative morbidity and mortality, prolonged duration of hospital stay, and additional medical costs. The purpose of this retrospective cohort study was to investigate the possible prevention of PPCs by intensive preoperative respiratory rehabilitation in esophageal cancer patients who underwent esophagectomy. The subjects included 100 patients (87 males and 13 females with mean age 66.5 ± 8.6 years) who underwent esophagectomy. They were divided into two groups: 63 patients (53 males and 10 females with mean age 67.4 ± 9.0 years) in the preoperative rehabilitation (PR) group and 37 patients (34 males and 3 females with mean age 65.0 ± 7.8 years) in the non‐PR (NPR) group. The PR group received sufficient preoperative respiratory rehabilitation for >7 days, and the NPR group insufficiently received preoperative respiratory rehabilitation or none at all. The results of the logistic regression analysis and multivariate analysis to correct for all considerable confounding factors revealed the rates of PPCs of 6.4% and 24.3% in the PR group and NPR group, respectively. The PR group demonstrated a significantly less incidence rate of PPCs than the NPR group (odds ratio: 0.14, 95% confidential interval: 0.02 ∼ 0.64). [Correction added after online publication 25 June 2012: confidence interval has been changed from −1.86 ∼ −0.22] This study showed that the intensive preoperative respiratory rehabilitation reduced PPCs in esophageal cancer patients who underwent esophagectomy.